2014
DOI: 10.1002/jmor.20251
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and cytochemical aspects of the germarium and the vitellarium in Syndesmis patagonica (Platyhelminthes, Rhabdocoela, Umagillidae)

Abstract: The cytoarchitecture of the female gonad of the endosymbiont umagillid Syndesmis patagonica has been investigated using electron microscopy and cytochemical techniques. The female gonad consists of paired germaria and vitellaria located behind the pharynx in the mid-posterior region of the body. Both the germaria and the vitellaria are enveloped by an outer extracellular lamina and an inner sheath of accessory cells which contribute to the extracellular lamina. Oocyte maturation occurs completely during the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
2
0
1
Order By: Relevance
“…Some previous studies on vitellogenesis in free-living and parasitic platyhelminths indicated that the ultrastructure of some vitelline cytoplasmic inclusions might differ, even between genera [10,13,33]. In the present study, the process of formation of vitelline cells in representative species of all diphyllobothriidean could be compared and related to their presumed phylogenetic position within the order Diphyllobothriidea.…”
Section: Possible Evolutionary Implications -Diphyllobothriideamentioning
confidence: 77%
“…Some previous studies on vitellogenesis in free-living and parasitic platyhelminths indicated that the ultrastructure of some vitelline cytoplasmic inclusions might differ, even between genera [10,13,33]. In the present study, the process of formation of vitelline cells in representative species of all diphyllobothriidean could be compared and related to their presumed phylogenetic position within the order Diphyllobothriidea.…”
Section: Possible Evolutionary Implications -Diphyllobothriideamentioning
confidence: 77%
“…For identification of peri-ischemic and contralateral area, 1–2 μm thick semithin sections were obtained with a porter Blum MT-1. Semithin sections were stained with 1% toluidine blue and 1% methylene blue in 1% sodium tetraborate [ 34 ] and observed under a Nikon Eclipse 80i light microscope (Nikon, Tokyo, Japan) ( Figure 4 ). From these sections, the isosceles trapezoid area was selected on the embedded tissue blocks to be further cut at ultramicrotome (Leica Microsystems, Wetzlar, Germany) to proceed with the ultrastructural analysis.…”
Section: Methodsmentioning
confidence: 99%
“…La mayoría de los trabajos realizados se centraron en aspectos relacionados al ciclo reproductivo y/o desarrollo embrionario del erizo comestible Loxechinus albus (Orler 1992;Pérez 2009;Pérez et al 2008Pérez et al , 2010Malanga et al 2009;Schuhbauer et al 2010), el erizo verde Arbacia dufresnii Parra et al 2015;Epherra et al 2015), el erizo acorazonado Abatus cavernosus (Gil et al 2009) y el erizo Pseudechinus magellanicus (Orler 1992;Marzinelli et al 2006Marzinelli et al , 2008. También se han realizado avances en algunos aspectos de la ecología trófica de Arbacia dufresnii (Penchaszadeh y Lawrence 1999;Teso et al 2009) y Pseudechinus magellanicus (Penchaszadeh et al 2004;Teso et al 2009), así como de otros aspectos ecológicos relacionados con su distribución espacial (Zaixso y Lizarralde 2000;Escolar 2010;Souto et al 2014) y relaciones interespecíficas (Pastorino y Zelaya 2001;Brögger y Ivanov 2010;Zelaya y Ituarte 2002Falleni et al 2014).…”
Section: Introducción Generalunclassified